1974
DOI: 10.1111/j.1532-5415.1974.tb05402.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Nona” Electrocardiogram: Findings in 100 Patients of the 90+ Age Group

Abstract: The electrocardiograms of 100 men and women, all past the age of 90, were analyzed for conduction times, axis deviation, summed frontal QRS and T amplitudes. The ECG patterns were classified, and limited clinical correlations were made. The heart rate, R‐T and QRS intervals remained virtually unchanged with age. An increase in PR intervals, a left axis shift and a reduction in summed frontal T values were noted. The high incidences of atrial fibrillation, left anterior hemiblock, extra systoles and delayed AV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Our study population showed a higher incidence of first-degree A-V block (27.7%) than previously detected by ambulatory ECG [1,2] and standard ECG in elderly pop ulation samples [18][19][20][21]. In this respect, we found that standard ECG is a faithful indica tor of first-degree A-V block.…”
Section: Discussionsupporting
confidence: 52%
“…Our study population showed a higher incidence of first-degree A-V block (27.7%) than previously detected by ambulatory ECG [1,2] and standard ECG in elderly pop ulation samples [18][19][20][21]. In this respect, we found that standard ECG is a faithful indica tor of first-degree A-V block.…”
Section: Discussionsupporting
confidence: 52%
“…The P-R interval, representing atrioventricular conduction, increases from 159 ms at ages 20–35 to 172 ms beyond age 60 26 . The QRS axis shifts leftward, possibly due to increases in LV wall thickness, with 20% of healthy subjects having a left axis deviation by age 100 27 . Interestingly, despite increased LV thickness, there is a decline in the R- and S-wave amplitudes with aging evident by age 40 28 .…”
Section: Cardiovascular Changes With Agingmentioning
confidence: 99%
“…Another important factor is the wall thickening of the LV in the elderly, which brings to a leftward axis shift of the QRS axis [ 19 ] and unlike expectations to a decline of the R-wave and S-wave amplitudes, which can be seen already by age 40 [ 20 ].…”
Section: Structural and Physiological Changes In Heart During Aginmentioning
confidence: 99%